Developing new product & marketing strategy case study tribute watch company - Fernaldy, Muhammad Yusuf; Wulansari, Amilia (Journal of Innovation, Business and Entrepreneurship, 2020)
Fashion is one of the creative industry sectors that provides the largest Gross Domestic Product (GDP) of 18.15 percent in this industrial sector among 15 other sectors. As the second biggest sub-sectors in the creative economy, the Fashion industry has promising growth. Until July 2018 fashion industry has made 8.2 Trillion USD in export. The number increase by 8.7 % compared with the year before. Fashion retailing has a low capital compared to other industries (Thanatassa). Because of the low capital, many newcomers to start a business in the fashion industry. The fashion industry has a wide variety of products. With so many fashion styles, a watch is one of the fashion apparel that can easily blend in with every fashion style, thus making it one of the most wanted products in the fashion industry. With so many competitions in the market, careful planning and an excellent product strategy are very crucial to help to win the market. Tribute Watch is a fashion company that wants to develop a new product for their customer. By developing a new product, Tribute Watch wants to improve its current product and gain an advantage in the market, especially in the fashion trend that changing rapidly nowadays.Thus the research question is What is the improvement feature for Tribute Watch, and what the marketing strategy for Tribute Watch new productThe researcher used the AIDA model to create the customer persona; from there, the researcher will generate based on the customer persona and the customers want. after the product has been generated, the researcher will create the marketing strategy based on the customer journey and the customer persona of Tribute Watch. This study uses a qualitative approach by conducting interviews with Tribute Watch customers. Interview results will be analyzed using a descriptive analysis approach. The number of respondents collected by the researcher is 15 person. The conclusion of this research is Tribute Watch's new product will be added several new features such as calendar, more optional strap, water resistance. Tribute Watch will brand themselves as a watch that can be used in every situation. For the marketing strategy, Tribute Watch will focus on online marketing, especially digital advertisements. Tribute watch marketing content will be based on the AIDA model which has a step to step to attract their customer systematicallyKeywords: Micro Watch Industries, New Product Development, AIDA model, Customer Persona, Marketing Strategy